Szubjektív Híradó 1994 május 8-29 két választás között
Mihály Kornis, Zoltán Farkas, József Barát, József Orosz, János Fiala, Miklós Győrffy, Zsuzsa Forgács, Iván Bedő, micro reports by Júlia Ránki, Ferenc Vicsek, György Nika, Katalin Rangos, Anikó Sándor, Péter Rózsa, Júlia Váradi, György Kakuk, András Bánó, László Kistamás, Sándor Szénási, György Nej, Endre Aczél, Ákos Szilágyi